Teaching clinical hematology and leukocyte differentiation in veterinary medicine using virtual patients - Marahrens, Hannah; Wagener, Matthias Gerhard; Schaper, Elisabeth; Zintl, Jana; Kiene, Frederik; Ganter, Martin (Frontiers in Veterinary Science, 2023)
Due to contact bans as a result of the COVID-19 pandemic, we created a new digital course on the Moodle learning platform for the winter semester 2020. In the clinical pathology course (CPC) with hematological content, third-year students were able to work independently on extra 10 digital cases of internal medicine of 8 different animal species as a compensation for reduction in microscopy exercises. Each case contained a preliminary report with the task of producing a differential blood count based on digitized blood smears. For each case, at least 100 leucocytes of archived blood smears had been previously photographed with a microscope camera. The cases were successive and increased in complexity, for example through the increase in the number of different cell types to be differentiated in the progress of the course. The participants had the opportunity to evaluate the course through a final module to rate user-friendliness and acceptance. The results of the participants of 2021 were analyzed descriptively, focusing on success rates, processing time, and attempts. A total of 237 (= 96%) of 247 students completed all cases, each assessing a total of 1033 photographs of blood cells. The mean processing time was 22.48 minutes for a differentiation and the students spent an average of 1.48 attempts on it. A voluntary feedback form was completed by 192 (= 78%) students, with more than 95% rating the course positively in 12 evaluation questions, and 29 of 33 comments (= 87.88%) formulating positive statements in a comment box. Suggestions for improvement primarily included more explanations on erythrocyte morphologies, followed by adjusting the difficulty level and improving the presentational set-up. Slight improvements in results, time spent on processing the tasks and the number of attempts indicated an achievement of routine and confidence during the course were associated with an increase of competences. The positive feedback showed a high acceptance of the digital format and students evaluated it as improving the quality of teaching in combination with practical exercises.